KONSTRUKSI IMPERSONAL DALAM BAHASA INGGRIS, SPANYOL, DAN INDONESIA - Japen Sarage (Kibas Cenderawasih : Jurnal Ilmiah Kebahasaan dan Kesastraan, 2019)
Impersonal construction can be viewed from two sides. First side is viewed from the sentence that do not have a subject or a subject in the form of words that do not show a particular referent or its existence tends formality. Second  is viewed from the impersonal construction which may include derivative words from sentences which have a clear subject. Based on the above, this study tries to discuss impersonal constructions in English, Spanish, and Indonesian or analyze a single sentence in Spanish, English, and Indonesian. The results showed that there are twokinds of impersonal constructions, namely dummy and empty subject. Impersonal construction has a single referent in Spanish can emerge a sentence one word, sentence subject can occupy a position of pre - verbal and post - verbal , and can conjugate with verbs according to gender , number and persona, while in English there is a rapprochement between the subject of the sentence and verbs or agreement based on the number. Copula in Spanish there are two items, namely ser and estar. In English ser and estar are represented by to be. English and Indonesian have similarity, which is the subject of the sentence is always pre - verbal position . Spanish, Indonesian, and English based on verbs of nature have similarity that are each laguages emerge impersonal construction.